EXTRACTION OF TITANIUM COMPOUNDS FROM CHLORIDE ACID SOLUTION OF BAUXITE RESIDUE USING ACID-BASE PRECIPITATION METHOD - Ernilia, Kristina; Silalahi, Imelda Hotmarisi; Zaharah, Titin Anita (Indonesian Journal of Pure and Applied Chemistry, 2024)
The bauxite residue from the Bayer process can be categorized into red cake and iron sand. In this paper the iron sand has been characterized and used as a research object in order to obtain material with a higher concentration of the titanium element. Iron sand has a dominant chemical content of 60% iron and 10% titanium. Titanium can be extracted by several methods, one of which is the precipitation method. The precipitation process involves dissolving minerals in an acidic solution and extracting them with a base. The type of base and the pH are factors that affect the precipitation process. The aim of this study is to determine the effect of variations in pH and type of base on the extraction of TiO2 from a solution of iron sand in hydrochloric acid and to determine the elemental composition of the precipitation product. The first treatment of the iron sands was magnetic separation, which yielded 31.76% of relatively weakly magnetic sand. The magnetic sand was leached by using HCl (25%) to result in a solid with a percentage recovery of 40.8%, followed by an alkali fusion reaction with NaOH to give 56.85% of material. This material was then dissolved in the concentrated HCl and precipitated with NH4OH and NaOH at various pH values. The elemental analysis by using XRF of the precipitation products shows that the precipitation in NH4OH and pH 8 gives the material with the highest content of the element Ti, which is 49.5%, increases from only 10% in the iron sand. The selectivity of titanium for the iron element seems to be higher for the precipitation in NaOH, pH 8 than in NH4OH, pH 8, with Ti/Fe ratios of 1.50 and 1.44, respectively